2016
DOI: 10.1016/j.afjem.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Professional needs of young Emergency Medicine specialists in Africa: Results of a South Africa, Ethiopia, Tanzania, and Ghana survey

Abstract: IntroductionEmergency Medicine (EM) residency programmes are new to Africa and exist in only a handful of countries. There has been no follow up on faculty development needs nor training of these graduates since they completed their programmes. The African Federation for Emergency Medicine (AFEM) aims to explore the needs of recent EM graduates with respect to the need for resources, mentorship, and teaching in order to develop a focused African faculty development intervention.MethodsAs part of the AFEM annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…These doctors are often the only specialist EM clinician in their country. As sole practitioners with little peer support, they must establish their credibility, explain the critical importance of their new specialty and take on substantial leadership roles . Burnout and premature career stagnation are substantial risks.…”
Section: Introductionmentioning
confidence: 99%
“…These doctors are often the only specialist EM clinician in their country. As sole practitioners with little peer support, they must establish their credibility, explain the critical importance of their new specialty and take on substantial leadership roles . Burnout and premature career stagnation are substantial risks.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this research does suggest that SGL may address some of the needs identified by Bae et al [2] in their survey of African EM specialists. SGL may be effective in increasing relationship building between learners and mentors, promoting active learning, and building more effective leadership and communication training.…”
Section: Resultsmentioning
confidence: 91%
“…A survey among recently graduated EM-trained specialists from the aforementioned African training programmes sought to characterise the challenges faced by the growing body of new EM practitioners. [2] The largest perceived needs were the lack of leadership development and training, including materials for training and 'active learning' , the need for improved relationships with faculty mentors, and the need for interprofessional communication training. Failure of the EM programmes to meet these needs has led to trainees leaving the field, a consequence noted by the first EM training programme developed in SA.…”
Section: Context Of Emergency Medicine Training In Sub-saharan Africamentioning
confidence: 99%
“…Following completion of the programme, graduates have a variety of opportunities in academics and private practice. In a survey of recent EMRP graduates, Bae and colleagues discovered that being a scholar and a manager were the two career areas for which EM physicians in Africa felt the least prepared as graduates and faculty 23. ‘Being a scholar’ meant having resources for conducting research and teaching, whereas ‘being a manager’ meant having access to leadership training.…”
Section: Discussionmentioning
confidence: 99%